Generalised Umbral Moonshine - Cheng, M.C.N.; de Lange, P.; Whalen, D.P.Z. (Symmetry, Integrability and Geometry: Methods and Applications, 2019)
Umbral moonshine describes an unexpected relation between 23 finite groups arising from lattice symmetries and special mock modular forms. It includes the Mathieu moonshine as a special case and can itself be viewed as an example of the more general moonshine phenomenon, which connects finite groups and distinguished modular objects. In this paper, we introduce the notion of generalised umbral moonshine, which includes the generalised Mathieu moonshine [Gaberdiel M.R., Persson D., Ronellenfitsch H., Volpato R., Commun. Number Theory Phys. 7 (2013), 145-223] as a special case, and provide supporting data for it. A central role is played by the deformed Drinfeld (or quantum) double of each umbral finite group G, specified by a cohomology class in H³(G, U(1)). We conjecture that in each of the 23 cases, there exists a rule to assign an infinite-dimensional module for the deformed Drinfeld double of the umbral finite group underlying the mock modular forms of umbral moonshine and generalised umbral moonshine. We also discuss the possible origin of the generalised umbral moonshine.